2012
DOI: 10.1364/oe.20.013082
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing guided-mode resonance band-pass filters: from 1D to 2D structures

Abstract: We study experimentally and theoretically band-pass filters based on guided-mode resonances in free-standing metal-dielectric structures with subwavelength gratings. A variety of filters are obtained: polarizing filters with 1D gratings, and unpolarized or selective filters with 2D gratings, which are shown to behave as two crossed-1D structures. In either case, a high transmission (up to ≈ 79 %) is demonstrated, which represents an eight-fold enhancement compared to the geometrical transmission of the grating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…Due to the high refractive index ( n ) and transparency, MOs have many applications in optical devices, such as gratings, photonic crystals, filters, antireflection layers, and biochemical sensors . Among all the available MOs, TiO 2 is particularly interesting.…”
Section: Solution Direct‐patterned Mo Micro‐ and Nanostructures For Omentioning
confidence: 99%
“…Due to the high refractive index ( n ) and transparency, MOs have many applications in optical devices, such as gratings, photonic crystals, filters, antireflection layers, and biochemical sensors . Among all the available MOs, TiO 2 is particularly interesting.…”
Section: Solution Direct‐patterned Mo Micro‐ and Nanostructures For Omentioning
confidence: 99%
“…More recently, a new kind of bandpass guided-mode resonance filter based on a metallic grating deposited on a single free-standing dielectric layer has been studied [9,10]. These filters are particularly well suited for infrared multispectral imaging applications [11,12] in terms of mechanical robustness, rejection efficiency, and quality factor.…”
mentioning
confidence: 99%
“…To circumvent this problem in the case of all-dielectric guided-mode resonance structures, Lemarchand et al have introduced a bi-atomic structure and demonstrated an increase of the angular tolerance without modifying the spectral lineshape [13,15]. However, this concept cannot be directly transposed to the metaldielectric structures of the papers [9,10]. Indeed, in this latter case, the nonradiative losses dominate and limit the influence of the grating shape.…”
mentioning
confidence: 99%
See 2 more Smart Citations